Battle Angel Alita : holy night & other stories - Kishiro, Yukito (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2018)
This deluxe collector's hardcover includes four classic Battle Angel Alita stories never before published in English, plus special bonus material! At long last, complete your Alita collection! This volume contains four manga short stories by Alita creator Yukito Kishiro, first published in Japan from 1997 to 2006: Holy Night, Supersonic Fingers, Homecoming, and Barjack Rhapsody. Plus exclusive bonus material.